Torsion Sensor with Rotation Direction Discrimination Based on a Pre-twisted In-Fiber Mach–Zehnder Interferometer - Zhiyong Bai; Mi Deng; Shen Liu; Zhe Zhang; JinShan Xu; Jian Tang; Ying Wang; Changrui Liao; Yiping Wang (IEEE Photonics Journal)
We demonstrate a torsion sensor with rotation direction discrimination based on a pre-twisted core-cladding mode Mach–Zehnder interferometer (MZI) fabricated in single mode fiber by twisting the fiber during CO2 laser irradiation to induce a permanent screw-type distortion at the two points of coupling between the core and cladding. The proposed sensor can measure the twist rate with a sensitivity of up to 10.35 nm/(rad/cm) and determine its rotation direction (i.e., clockwise or counterclockwise) simultaneously. Furthermore, the sensitivity of the torsion sensor can be enhanced by increasing the initial shear strain.